Competition, competitive advantage, and clusters the ideas of Michael Porter - Huggins, Robert; Izushi, Hiro. (Oxford : Oxford University Press, 2011)
In this book leading scholars from a range of disciplines including strategic management, economic development, economic geography and planning, assess the contribution that Michael Porter, one of the most influential figures in strategic management research, has made to these respective academic fields.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Porter, Michael E., -- 1947- -- Influence; Strategic planning; Competition; Competition, International; Industrial clusters